Value-Based Performance Excellence Measurement For Higher Education Institution: Instrument Validation - M. R., Abdul Hamid; Zainol, Mustafa; Nur Riza, Mohd Suradi; Fazli, Idris; Mokhtar, Abdullah (Springer, 2012)
The purpose of this article is to construct-validate an instrument of value-basedperformance excellence measurement for higher education institution (HEI) in Malaysia. The HEI performance is measured using 6 value indicators of leadership, culture, productivity, employee, stakeholders and overall performance. 1,100 questionnaires were distributed and 275 questionnaires were used for analysis. Confirmatory factor analysis (CFA) approach was deployed by using analysis of moment structures software. The results for the hypothesised CFA model revealed the fit statistics of CFI = 0.944, TLI = 0.939 and RMSEA = 0.075. In conclusion, the CFA model fitted the data well. Implications of the study was significant to HEI to consider and adapt the value-based assessment approach in university assessment for total excellence.